2017
DOI: 10.1039/c6tc04808k
|View full text |Cite
|
Sign up to set email alerts
|

Chiral recognition of optically active CoFe2O4magnetic nanoparticles by CdSe/CdS quantum dots stabilised with chiral ligands

Abstract: We report a new optical sensing approach based on the chiral recognition of optically active CoFe2O4magnetic nanoparticles by CdSe/CdS core/shell quantum dots stabilized with cysteine of different chiralities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 53 publications
1
28
0
1
Order By: Relevance
“…After the synthesis of the QDs, optical activity was induced by exchange of the original oleylamine ligands with D‐ and L‐Cys ligands . It has been demonstrated before that the ligand exchange method used in this work does not influence either the size or morphology of QDs . Absorption and PL spectra of the QDs before and after the ligand exchange are presented in Figure .…”
Section: Resultsmentioning
confidence: 81%
See 1 more Smart Citation
“…After the synthesis of the QDs, optical activity was induced by exchange of the original oleylamine ligands with D‐ and L‐Cys ligands . It has been demonstrated before that the ligand exchange method used in this work does not influence either the size or morphology of QDs . Absorption and PL spectra of the QDs before and after the ligand exchange are presented in Figure .…”
Section: Resultsmentioning
confidence: 81%
“…26 It has been demonstrated before that the ligand exchange method used in this work does not influence either the size or morphology of QDs. 41 Absorption and PL spectra of the QDs before and after the ligand exchange are presented in Figure 2. The edge of the first exciton absorption band was located at 300 nm approximately.…”
Section: Optical Properties Of Zns:mn Qdsmentioning
confidence: 99%
“…Colloidal semiconductor nanoparticles with a chiral optical response are a new subclass of nanomaterials which have recently attracted significant attention due to a variety of potential applications . These nanostructures combine the tunability and control afforded by quantum confinement effects with unique properties which render them as potential candidates for use in chiral sensing, asymmetric catalysis, quantum optics, and spintronics . A limited range of semiconductor nanocrystals, such as cinnabar HgS, exhibit a chiral crystal structure and are therefore intrinsically chiral .…”
Section: Introductionmentioning
confidence: 99%
“…This ligand was chosen due to its biocompatibility, low cost, chiral nature, stability and simplicity, avoiding the addition of any undesired functionality, or toxic effects. In addition, recent studies have shown that MNPs synthesised in the presence of chiral ligands can display novel optical properties …”
Section: Figurementioning
confidence: 99%